Predicting Cultivation Area, Production, and Yield of Maize in Nepal: An ARIMA Model Approach - Poudel, Bibas (Nepalese Journal of Statistics, 2024)
Background: Maize is the primary cereal crop of Nepal after rice. It is the major component of feed for the livestock and poultry sectors. The current maize yield is unable to meet its increasing demand in Nepal. Hence, substantial quantities of maize are being imported to fill the gap. Accurate forecasting of maize cultivation area, production, and yield is critical for successful market stabilization and sustainable agricultural practice promotion. Objective: The study aims to predict the cultivation area, production, and yield of maize in Nepal from 2023/24 to 2029/30 using appropriate Autoregressive Integrated Moving Average (ARIMA) models. Materials and Methods: The study uses time series data from 1963/64 to 2022/23 covering maize area (ha), production (Mt), and yield (Mt/ha), obtained from the Ministry of Agriculture and Livestock Development and Agriculture Information and Training Center. The Box-Jenkins methodology-based ARIMA model was used for modeling and forecasting the future time series data. The estimated models were further diagnosed to validate no significant autocorrelation among residuals. Results: The Box-Jenkins methodology demonstrated ARIMA (4, 1, 0), ARIMA (1, 1, 1) and ARIMA (1, 1, 1) models for forecasting maize cultivation area, production, and yield, respectively. The study predicts a 4.84% increase in maize cultivation area, a 6.83% rise in production, and a 3.17% improvement in yield from 2023/24 to 2029/30. However, these increases are not projected to meet Nepal's rising maize demand. Conclusion: The study findings are relevant for ensuring import/export management and implementing the price policy in Nepal. The research highlights the need for technological advancements and improved management practices in maize production to ensure long-term sustainability.